2018
DOI: 10.1002/jca.21634
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of αβ+ T cells for a haploidentical hematopoietic stem cell transplantation in children

Abstract: A consistent and reproducible depletion technique is crucial for the successful transplantation of an ex vivo depleted graft. Our aim was to evaluate the efficacy of an ex vivo technique for depletion of αβ T cells using a biotinylated anti-TCRαβ monoclonal antibody, which was performed by one clinical nurse specialist. Between 2012 and 2017, 119 depletion procedures from 216 apheresis using the anti-TCRαβ monoclonal antibody were performed on 105 pediatric patients. The median log depletion of αβ T cells was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 26 publications
1
10
1
1
Order By: Relevance
“…This study reports the accumulated experience of all Spanish centers performing haplo‐HSCTs for the pediatric population with NMDs, which corresponds to 13.9% of the cumulative activity of haplo‐HSCTs 30 . In our study, the 2‐year OS of 44.9% was lower than that in our reported series on malignant disorders (55.1%) 26 and that recently reported from various groups in NMDs, which also differed according to the diagnosis 2,12,28,29,36‐39 . These differences can be explained by the fact that haplo‐HSCT in NMDs was not a routine practice in the first decade of this study (2001‐2010), with matched sibling donors the first option for PIDs and other NMDs.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…This study reports the accumulated experience of all Spanish centers performing haplo‐HSCTs for the pediatric population with NMDs, which corresponds to 13.9% of the cumulative activity of haplo‐HSCTs 30 . In our study, the 2‐year OS of 44.9% was lower than that in our reported series on malignant disorders (55.1%) 26 and that recently reported from various groups in NMDs, which also differed according to the diagnosis 2,12,28,29,36‐39 . These differences can be explained by the fact that haplo‐HSCT in NMDs was not a routine practice in the first decade of this study (2001‐2010), with matched sibling donors the first option for PIDs and other NMDs.…”
Section: Discussioncontrasting
confidence: 51%
“…30 In our study, the 2-year OS of 44.9% was lower than that in our reported series on malignant disorders (55.1%) 26 and that recently reported from various groups in NMDs, which also differed according to the diagnosis. 2,12,28,29,[36][37][38][39] These differences can be explained by the fact that haplo-HSCT in NMDs was not a routine practice in the first decade of this study (2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010), with matched sibling donors the first option for PIDs and other NMDs. It should also be noted that the patients in our series were at major risk because, in most cases, there can be significant delays between the diagnosis and transplantation, leading to increased cumulative morbidity, thereby contributing to high post-…”
Section: Discussionmentioning
confidence: 94%
“…Historically, the majority of studies relating to haploid HSCT have focused on T-cell depletion from grafts in vitro or on the use of cyclophosphamide post-transplantation. [7][8][9][10] However, the incidence of GF and GVHD remains prominent problems. It has been reported that the unmanipulated haploid HSCT regimen, which consisting of the grafts of BM and PBSCs mobilized by G-CSF, in addition to antithymoglobulin, obtained good clinical efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Human Vγ9Vδ2 T cells can directly kill leukemia cells 9 without causing graft versus host disease (GVHD) 10 . It has been proven that the depletion of αβ T cells is a safe and effective tumor therapy 11 . Clinical studies are underway to activate γδ T cells by administering Zol after αβ T and B cell‐depleted hematopoietic stem cell transplantation (HSCT) to obtain an optimal therapeutic effect based on the activity of γδ T cells 12,13 .…”
Section: Introductionmentioning
confidence: 99%